Symposium on the report of the Commission on Social Welfare - Dowling, Brendan R. (Statistical and Social Inquiry Society of Ireland, 1987)
The Report of the Commission on Social Welfare represents a philosophical and economic view of Irish society that since independence has failed to command more than a fraction of popular support. More important, perhaps, the Commission has ignored many of the issues set out in the terms of reference. The report can be summarised very simply - it believes that social welfare payments are too low and that taxes should be increased on public servants, the self-employed including farmers, and those with incomes over #14,700 per annum to pay for these increases. It finds virtually nothing wrong with the social security system - other than the minutiae of operations - and the major recommendations deal with mechanisms for increasing public spending on social welfare. It is difficult to know how to approach a critique of the report so profound is my objection to it. However the best approach might be to comment on each Chapter, laying particular emphasis on those areas where the report errs, either by omission or commission.
The report of the Commission on Social Welfare
Read before the Society, 30th October, 1986
Keywords: Social welfare; Social conditions; 314.15